Hero-Honda - Barua, S. K. (SAGE knowledge. Cases., 2016)
The case focuses on governance issues that arise in case of joint ventures. The case is based on one of the most successful joint ventures in the history of corporate India between Honda Motor Company of Japan and the Munjal family of India. They established Hero Honda Motor Company in 1984. The company became the largest producer of motorcycles in the world.